1996
DOI: 10.1007/bf00993645
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype analysis of the sea urchinParacentrotus lividus (Echinodermata): evidence for a heteromorphic chromosome sex mechanism

Abstract: A consistent diploid number of 2n = 36 was determined for the sea urchin Paracentrotus lividus from the Gulf of Palermo by analysis of mitotic chromosomes of both early developing embryos and male gonads. The haploid number n = 18 was determined by counts of spermatocyte bivalents at diakinesis. A heteromorphic chromosome sex mechanism of the XY type is likely present in this species. This is indicated by the occurrence of a chromosomal pair, pair No. 2, which is heteromorphic in both morphology and size in ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
0
22
1
Order By: Relevance
“…Sex ratios have, however, been used as a broadscale diagnostic indicator of the mode of reproduction (Sadovy and Shapiro 1987;Williamson and Steinberg 2002) and our data conform to those for gonochorism in Echinometra from the GOA/E and Okinawa (sex ratio of 1:1), and although male predominance was recorded in Echinometra populations from Zanzibar, no hermaphrodites were observed in any of the samples. Species with a chromosomal (i.e., genetic) sex determination mechanism, such as Paracentrotus lividus (Lipani et al 1996), are expected to allocate equal effort to producing male and female offspring because random meiosis would lead to a mean sex ratio of 0.5 (Gianguzza et al 2009). Thus, as largely no size differences or sex ratio disparities were observed between the two sexes across highly diverse environments, sex allocation in Echinometra appears to be an inherent trait with little sexual plasticity in respect to environmental conditions.…”
Section: Sex Ratios and Allometrymentioning
confidence: 99%
“…Sex ratios have, however, been used as a broadscale diagnostic indicator of the mode of reproduction (Sadovy and Shapiro 1987;Williamson and Steinberg 2002) and our data conform to those for gonochorism in Echinometra from the GOA/E and Okinawa (sex ratio of 1:1), and although male predominance was recorded in Echinometra populations from Zanzibar, no hermaphrodites were observed in any of the samples. Species with a chromosomal (i.e., genetic) sex determination mechanism, such as Paracentrotus lividus (Lipani et al 1996), are expected to allocate equal effort to producing male and female offspring because random meiosis would lead to a mean sex ratio of 0.5 (Gianguzza et al 2009). Thus, as largely no size differences or sex ratio disparities were observed between the two sexes across highly diverse environments, sex allocation in Echinometra appears to be an inherent trait with little sexual plasticity in respect to environmental conditions.…”
Section: Sex Ratios and Allometrymentioning
confidence: 99%
“…(1) P. lividus embryos are supplied continuously as experimental material since they are routinely employed in molecular assays; 12 and (2) mitotic chromosomes of this species 13 are considerably larger than those of C. intestinalis, thus allowing us to better evaluate possible chromosome abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…1b are most likely the NOR-bearing ones. In fact, Lipani et al (1996) reported Ag-NORs on three pairs of homologs (no. 5, 8 and 12) characterized by G-negative interstitial bands on the long chromosome arms.…”
Section: Resultsmentioning
confidence: 99%
“…Here we report for the first time the chromosomal localization of 5S rDNA in a species of echinoderms, Paracentrotus lividus, which, compared to other echinoderms, has an exceptionally low chromosome number, 2n = 36 (Boveri, 1902). Its karyotype is composed of one pair of large submetacentric chromosomes, a pair of sex-specific heteromorphic chromosomes, and 16 pairs of subtelocentric chromosomes (Lipani et al, 1996).…”
Section: Rationale and Significancementioning
confidence: 99%